2020
DOI: 10.1097/brs.0000000000003643
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Vertebral Body Tethering for Adolescent Idiopathic Scoliosis

Abstract: Study Design. Retrospective analysis of prospectively collected data. Objective. To report the follow-up curve behaviors in different Sanders staging groups. Summary of Background Data. Vertebral body tethering (VBT) is a growth modulation technique that allows gradual spontaneous follow-up curve correction as the patient grows. There is a lack of scientific evidence regarding appropriate patient selection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 26 publications
0
54
1
2
Order By: Relevance
“…A further 137 studies were excluded for the following reasons: not matching the topic of interest (n = 107), not a clinical study (n = 19), insufficient clinical details or insufficient follow-up (n = 8), fewer than 5 patients (n = 1). Nine studies met all inclusion criteria and were analysed for the present study 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 . The literature search is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further 137 studies were excluded for the following reasons: not matching the topic of interest (n = 107), not a clinical study (n = 19), insufficient clinical details or insufficient follow-up (n = 8), fewer than 5 patients (n = 1). Nine studies met all inclusion criteria and were analysed for the present study 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 . The literature search is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Weitere 137 Studien wurden aus folgenden Gründen ausgeschlossen: thematisch nicht zutreffend (n = 107), keine klinische Studie (n = 19), unzureichende klinische Angaben oder nicht ausreichendes Follow-up (n = 8), weniger als 5 Patienten (n = 1). Neun Studien erfüllten alle Einschlusskriterien und wurden für die vorliegende Arbeit analysiert 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 . Die Literaturrecherche ist in Abb.…”
Section: Ergebnisseunclassified
“…Miyanji et al published on 55 immature patients Risser 0.5 showing clinical success in 77% and 8% insufficient correction requiring conversion to PSF ( 19 ). Alanay et al reported on mature cohort of Sanders score 6–7 with 100% success, 55% correction and residual curve (9°–27°) at 20 months and Meyers et al reported on 49 mature patients with 76% success, 41% tether breakage and 2% revision with PSF at 32.5 months ( 8 , 26 ). Figures 4 – 6 showcase a 14-year-old female (Sanders 7) that underwent T12-L4 anterior tethering with correction of the curve from 42° to 17° postoperatively and the patient being well balanced at 6-months post surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Newton et al was first to report that skeletally immature patients continue to correct and even go to overcorrection to 121% as compared to mature adolescents whose tethers act as permanent tether rather than as true growth modulators ( 9 , 23 , 24 ). Alanay and colleagues noticed that overcorrection and mechanical complications are more common in Sanders 2 group ( 26 ). Such observation is avoided by delaying VBT until patient skeletally matures to Sanders stage 3 and is treated with removal of tether to avoid further curvature modification ( 23 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Primary stability is an important requirement for VBT implants, and it would be preferred if the implants last at least until skeletal maturity, which in some cases, could last a few years from the time of surgery. Short-term success rates (no fusion required) after VBT have been observed [27], but tether breakages seem to be one of the most frequently observed implant-related complications, which may make results after VBT less predictable. However, the definition of success remains controversial.…”
Section: Discussionmentioning
confidence: 99%